Comparison of clinical characteristics and outcomes in patients with left bundle branch block versus ST-elevation myocardial infarction referred for primary percutaneous coronary intervention. Issue 1 (January 2015) - Mozid, Abdul M.; Mannakkara, Nilanka N.; Robinson, Nicholas M.; Jagathesan, Rohan; Sayer, Jeremy W.; Aggarwal, Rajesh K.; Clesham, Gerald J.; Tang, Kare H.; Kelly, Paul A.; Davies, John R.; Gamma, Reto A.
Abstract : Aims: Recent studies have suggested that a low proportion of patients presenting with left bundle branch block (LBBB) require emergency intervention. In this study, we have compared baseline clinical characteristics, angiographic findings and subsequent outcomes in patients with LBBB versus ST-elevation myocardial infarction (STEMI) referred to our tertiary centre for primary percutaneous coronary intervention (PCI). Methods and results: A large retrospective observational study was performed involving 1875 consecutive patients presenting to our single tertiary cardiac centre for primary PCI over a 27-month period. Patients presenting with LBBB ( n =155, 8.3%) were significantly older ( P <0.0001) and were more likely to be female ( P <0.0001) and have a prior history of myocardial infarction ( P <0.0001) or coronary artery bypass graft surgery ( P =0.005). Rates of acute occlusion (12.2 vs. 63%; P <0.0001) and PCI (26 vs. 83%; P <0.0001) were significantly lower in LBBB patients compared with STEMI patients. Although the 30-day mortality was similar, overall mortality during the 2 years of follow-up was significantly higher in the LBBB group compared with the STEMI group (27.8 vs. 13.9%; P =0.023). Conclusion: The incidence of an acutely occluded vessel is low in LBBB when compared with STEMI, but the long-term outcome is significantly worse. Patients with LBBB referred for primary PCI need better risk stratification, and further work is needed to identify potential diagnostic and management strategies.